2019
DOI: 10.17159/sajs.2019/6221
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural practices and their potential role in mycotoxin contamination of maize and groundnut subsistence farming

Abstract: Mycotoxigenic fungi are common pathogens of maize and groundnuts; they produce mycotoxins which reduce the yield and quality of these grain crops. Numerous agricultural practices including crop rotation and storage methods have been shown to impact mycotoxin accumulation. Therefore, the farming and storage practices in maize and groundnut subsistence farming systems in Pongola, Vryheid, Jozini, Manguzi and Mbazwana Districts of northern KwaZulu-Natal (South Africa) were surveyed to determine their potential ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…These results support findings by Matumba et al [32], that large proportion of rural Malawians were not aware of effective control measures of mycotoxins in foodstuffs. Similar, other researchers reported that there is limited information in developing countries on control strategies of mycotoxins contamination in food commodities Phokane et al [46], Torabi et al [47]. From the findings of the present study, inadequate knowledge of food handlers on mycotoxins control may risk school children from consuming maize foods contaminated with toxins.…”
Section: Knowledge Of the Respondents About Control Measures Of Mycotsupporting
confidence: 79%
“…These results support findings by Matumba et al [32], that large proportion of rural Malawians were not aware of effective control measures of mycotoxins in foodstuffs. Similar, other researchers reported that there is limited information in developing countries on control strategies of mycotoxins contamination in food commodities Phokane et al [46], Torabi et al [47]. From the findings of the present study, inadequate knowledge of food handlers on mycotoxins control may risk school children from consuming maize foods contaminated with toxins.…”
Section: Knowledge Of the Respondents About Control Measures Of Mycotsupporting
confidence: 79%
“…Maize (Zea mays) production has been very volatile, with generally poor quality, being predominantly of white maize type with lower content on β-carotene [95]. Yellow maize grain and transgenic species from multinationals are imported from South Africa and not common and relatively few grain processing services are available [96], [97]. While maize production in Mozambique has been reported as 1,9 million tons for 2020/21, there is heavy informal cross border trade across the region rendering production estimates redundant although maize supplies likely meet national food consumption needs [98].…”
Section: Maizementioning
confidence: 99%
“…Crop rotation and intercropping can reduce the mycotoxin contamination in maize and groundnut, and in conservation agriculture (e.g., permanent soil cover and minimum soil disturbance) can decrease the risk of contamination [ 37 ]. Monoculture of maize under conventional tillage compared to no-tillage monoculture and no-tillage two- or three-year rotation (consisting of maize/cowpea and maize/cowpea/babala, respectively) showed no significant differences in terms of fumonisin contamination in South Africa [ 38 ]. Baliukonienè et al [ 39 ] found a higher contamination of aflatoxins and deoxynivalenol (DON) in cereals from no-tillage farming systems than conventional farming systems (+14 and +24%, respectively).…”
Section: Systems For the Control Of Mycotoxins In Feed And Foodmentioning
confidence: 99%